Cobalt-based coordination polymer for lithium-ion battery electrode materials and preparation method thereof

The synthesis of one-dimensional cobalt-based coordination polymer material Co-CP by solvothermal method solves the problem of low capacity and easy dissolution of the positive electrode material of lithium-ion batteries, achieving high specific capacity and excellent cycle stability, and having broad application prospects.

CN116217960BActive Publication Date: 2025-04-08CHANGZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310320719.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-27
Publication Date
2025-04-08
Estimated Expiration
2043-04-27

AI Technical Summary

Technical Problem

The actual capacity of the positive electrode material of the existing lithium-ion battery is lower than the theoretical capacity, and the specific capacity rapidly declines after multiple charges and discharges, and the organic carbonyl compounds are easily dissolved and have low conductivity in the electrolyte.

Method used

The one-dimensional cobalt-based coordination polymer material Co-CP was synthesized by solvothermal method, and 2,7-(1,2,4-tetrazolyl)benzophenylaloline tetraone, isoindole diacetic acid and cobalt salt were used as raw materials to produce Co-CP material with excellent properties.

Benefits of technology

Co-CP materials exhibit excellent cycling stability and high specific capacity. The first discharge specific capacity is 247mAh g-1. After 50 cycles, the Coulomb efficiency is close to 100%, which is better than the inorganic positive electrode materials used on the market.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116217960B_ABST
    Figure CN116217960B_ABST
Patent Text Reader

Abstract

The invention belongs to the field of synthesis of lithium ion battery positive electrode materials, and relates to a cobalt-based coordination polymer material and a preparation method and application thereof, wherein the preparation steps are as follows: 2,7-(1,2,4-tetrazolyl)benzophenanthroline tetraketone (4-DTBPT) is ultrasonically dissolved in an appropriate amount of organic solvent, and then an appropriate amount of distilled water and isoindolediacetic acid (BGPD) are added, and after being fully dissolved, all are transferred to an autoclave, an appropriate amount of cobalt salt is weighed and placed in the autoclave, and a reaction is carried out in an oven, and after cooling, pink strip crystals are obtained by filtering. The molecular formula of the crystals is C 52 H 38 CoN 18 O 20 (Co‑CP). It has broad application prospects in the field of lithium-ion battery electrode materials. The synthesis method of the present invention is simple, easy to produce, low in cost, and has good reproducibility. It is a new inorganic-organic hybrid electrode material and has broad application prospects in the fields of energy storage systems such as lithium batteries and wearable devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation of lithium battery electrode materials, and in particular relates to a cobalt-based coordination polymer material and a preparation method thereof. Background Art

[0002] At present, developing high-performance rechargeable batteries is one of the means to solve the energy crisis problem that is becoming increasingly concerned. Lithium-ion batteries have broad application prospects due to their high energy density and have become energy storage systems for various electric vehicles and electronic products. One of the core components of lithium-ion batteries is the positive electrode material, which directly affects the performance of lithium-ion batteries. The positive electrode materials currently on the market are inorganic metal oxides such as LiCoO2 or LiFePO4. However, factors such as incomplete lithium removal in its structure and the insulating layer formed on the surface of the metal oxide cause the actual capacity of the battery to be far lower than the theoretical capacity. After multiple charge and discharge, the specific capacity rapidly declines. In addition, as a substitute for metal oxides, organic matter has also been widely studied and used as a positive electrode active material. Among them, organic carbonyl compounds have received particular attention due to their high theoretical specific capacity and fast kinetics, but this type of material also faces the problem of being easily soluble in the electrolyte and having low conductivity. In order to overcome these problems, many methods have been proposed, one of which is to coordinate organic carbonyl compounds with metal ions to synthesize metal coordination polymers (J. Am. Chem. Soc. 2014, 136, 16112-16115).

[0003] Coordination polymers (CPs) are a class of compounds composed of organic ligands and metal ions or metal clusters, containing three-dimensional, two-dimensional and one-dimensional structures bonded by coordination. Among them, two-dimensional and three-dimensional porous CPs are usually referred to as metal organic frameworks (coordination polymers). This type of material shows a wide range of potential applications in magnetic materials, energy storage, sensors, gas separation and storage, catalysis and drug delivery (Nature 2016, 539, 76-80; Chem. Eng. J. 2022, 431, 133234). Because they can provide redox-active metal ions and organic ligands, as well as pores for electrolyte ion shuttles, and even flexible structures that can overcome the pulverization and volume effects of some electrode materials, coordination polymers / CPs have been directly used as positive electrode materials for lithium-ion batteries and have attracted attention in recent years. The Tarascon research group reported in 2007 that 3D iron-based coordination polymer materials (FeⅢ(OH) 0.8 F 0.2 [O2C-C6H4-CO2], MIL-53(Fe)) as the positive electrode material of lithium-ion batteries. Although this material has a low theoretical capacity of 70 mAh g -1, but has excellent cycling performance (Angew. Chem. Int. Ed. 2007, 46, 3259-3263.).

[0004] Since constructing metal coordination polymers can effectively overcome the dissolution problem of organic electrodes, it is feasible to find inorganic-organic hybrid positive electrode materials with high specific capacity from coordination polymers, which can be applied in practical fields and are environmentally friendly and economical. Summary of the invention

[0005] The purpose of the present invention is to provide a simple and easy preparation method of a benzophenanthroline tetraketone derivative type coordination polymer material, and to study its performance as a lithium battery electrode material. Specifically, a one-dimensional cobalt-based coordination polymer material Co-CP and its preparation method and application are provided. The method uses readily available raw materials and adopts a solvothermal method to synthesize a cobalt-based coordination polymer material with a high yield, and its molecular formula is C 52 H 38 CoN 18 O 20 (Co-CP). This method has simple process, low cost, low energy consumption, good reproducibility and excellent performance. When used as the positive electrode material of lithium battery, it has excellent cycle stability and high specific capacity. The specific capacity of Co-CP in the first discharge is 247mAh g -1 After 50 cycles, the discharge capacity is 213 mAh g -1 , which is higher than the specific capacity of the inorganic positive electrode materials lithium cobalt oxide LiCoO2 and lithium iron phosphate LiFePO4 used on the market, and its coulombic efficiency is almost close to 100%.

[0006] One-dimensional cobalt-based coordination polymer material Co-CP, the structural formula is as follows:

[0007]

[0008] The present invention also provides a method for synthesizing the Co-CP, comprising generating Co-CP by solvent thermal reaction of 2,7-(1,2,4-tetrazolyl)benzophenanthroline tetraketone, isoindolediacetic acid and cobalt salt in N,N'-dimethylformamide and distilled water.

[0009] The specific steps include:

[0010] (1) Synthesis steps of 2,7-(1,2,4-tetrazolyl)benzophenanthroline tetraketone (4-DTBPT):

[0011] Under the protection of inert gas, 1,4,5,8-naphthalenetetracarboxylic anhydride (NTCDA), 4-amino-1,2,4-triazole (4-AT) and an organic solvent are added to the reactor, and after repeated dissolution and uniform dispersion, the mixture is continuously stirred and heated to reflux temperature. The reaction is stopped after 15 hours, cooled in an ice bath after reaching room temperature, anhydrous ether is added, and the mixture is filtered after standing for 4 hours. Finally, it is washed with ether for 2-3 times and vacuum dried to obtain the product, which is 2,7-(1,2,4-tetrazolyl)benzophenanthroline tetraketone (4-DTBPT).

[0012] (2) Synthesis steps of isoindolediacetic acid (BGPD):

[0013] Add pyromellitic anhydride and an organic solvent to a reactor, heat to a temperature to dissolve the pyromellitic anhydride, then add glycine and heat under reflux for 4 hours. Then filter while hot to obtain a precipitate. Place the precipitate in deionized water, heat to 80°C and stir, then recrystallize at low temperature, and dry in a vacuum oven to obtain the product, which is isoindolediacetic acid (BGPD).

[0014] 2,7-(1,2,4-tetrazolyl)benzophenanthroline tetraketone (4-DTBPT) synthesis formula:

[0015]

[0016] Furthermore, the inert gas is one of nitrogen or argon.

[0017] Furthermore, the ratio of 1,4,5,8-naphthalenetetracarboxylic anhydride (NTCDA) to 4-amino-1,2,4-triazole (4-AT) is 1:2-1:2.2.

[0018] Furthermore, the organic solvent is N,N'-dimethylformamide

[0019] Synthesis formula of isoindolediacetic acid (BGPD)

[0020]

[0021] Furthermore, the molar ratio of pyromellitic anhydride to glycine is 1:2-1:2.2.

[0022] Furthermore, the organic solvent is glacial acetic acid.

[0023] (3) Synthesis steps of Co-CP:

[0024] Co-CP was synthesized by solvothermal reaction of 2,7-(1,2,4-tetrazolyl)benzophenanthrolinetetraone (4-DTBPT), isoindolediacetic acid (BGPD) and cobalt salt in organic solvent and distilled water.

[0025] 2,7-(1,2,4-tetrazolyl)benzophenanthroline tetraketone (4-DTBPT) was ultrasonically dissolved in an appropriate amount of organic solvent, and then an appropriate amount of distilled water and isoindolediacetic acid (BGPD) were added. After being fully dissolved, all of them were transferred to an autoclave, and an appropriate amount of cobalt salt was weighed and placed in the autoclave. The reaction was heated (the reaction condition was preferably 80°C for 24h), and then filtered after cooling to obtain pink strip crystals. The crystal structure formula is [Co(DTBPT)(DMF)2(H2O)2](DTBPT)(C 10 H4O8), the molecular formula of the crystal is C 52 H 38 CoN 18 O 20 (Co-CP).

[0026] Furthermore, the molar ratio of the 2,7-(1,2,4-tetrazolyl)benzophenanthroline tetraketone (4-DTBPT), isoindolediacetic acid (BGPD) and cobalt salt is 1:2:2-1:2.2:2.2.

[0027] Furthermore, the solvent is N,N'-dimethylformamide, and the DMF molecules are retained in the Co-CP formed in the coordination polymer.

[0028] Furthermore, the volume ratio of the distilled water to the organic solvent is 1:2-1:2.2.

[0029] Furthermore, the cobalt salt is Co(NO3) 2. 6H2O、CoSO 4. 7H2O、CoCl 2. One of 6H2O, (CH3COO)2Co.

[0030] Furthermore, the oven reaction temperature is 80°C.

[0031] Furthermore, the cooling rate is 5-10°C / h.

[0032] Compared with the prior art, the present invention has the following advantages:

[0033] The present invention adopts a solvothermal method to prepare Co-CP, which has simple process, low cost, low energy consumption, good reproducibility and excellent performance. Co-CP can solve the problem of dissolving the organic material 2,7-(1,2,4-tetrazolyl)benzophenanthroline tetraketone in the electrolyte. Yuan et al. from Shanghai University synthesized Fe-HTANAT coordination polymer with hexaazinapthyltricarboxylic acid (HTANTA) as a ligand, showing good electrochemical performance. In comparison, the performance of Co-CP and Fe-HTANTA is almost the same, but the price of the ligand used in Co-CP is more advantageous (CN 109273715A). This type of material has excellent cycle stability and high specific capacity as an electrode material for lithium-ion batteries. It is a new type of organic electrode material with broad application prospects in energy storage systems such as lithium batteries and wearable devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 is the infrared spectrum of Co-CP;

[0035] Figure 2 is the powder X-ray diffraction spectrum of Co-CP;

[0036] Figure 3 is the thermogravimetric spectrum of Co-CP;

[0037] Figure 4 The nitrogen adsorption-desorption isotherm and pore size distribution curve of Co-CP

[0038] Figure 5 is the scanning electron microscope image of Co-CP;

[0039] Figure 6 TEM image of Co-CP;

[0040] Figure 7 is the coordination environment diagram of Co-CP;

[0041] Figure 8 It is the one-dimensional structure diagram of Co-CP;

[0042] Fig. 9 is the three-dimensional stacking diagram of Co-CP;

[0043] Fig.10 is the cyclic voltammogram of Co-CP;

[0044] Fig.11 is the charge and discharge diagram of Co-CP;

[0045] Fig.12 is the cycling stability diagram of Co-CP;

[0046] Fig.13 is the AC impedance diagram of Co-CP; DETAILED DESCRIPTION

[0047] The present invention will be further described below by means of specific embodiments:

[0048] Embodiment 1:

[0049] In a 250mL three-necked flask, 60mL of dehydrated N,N'-dimethylformamide (DMF) was added, and after passing N2 for about 5 minutes, 1,4,5,8-naphthalenetetracarboxylic anhydride (NTCDA) (3mol, 0.805g) and 4-amino-1,2,4-triazole (4-AT) (6mol, 0.504g) were added in sequence. The mixture was stirred magnetically and heated to reflux for 15 hours, then cooled to room temperature and then cooled in an ice bath. 120mL of anhydrous ether was added, and after standing for 4 hours, the mixture was filtered, washed with ether 2-3 times, and dried in a vacuum drying oven at 80°C for 3 hours to obtain the product 2,7-(1,2,4-tetrazolyl)benzophenanthrolinetetraone (4-DTBPT).

[0050] Add 60 mL of glacial acetic acid to a 250 mL three-necked flask, then weigh pyromellitic anhydride (10 mmol, 2.18 g) into the three-necked flask, and then heat to 120 ° C. After the pyromellitic anhydride is dissolved, weigh glycine (20 mmol, 1.5 g) into the three-necked flask. Heat and reflux for 4 hours. Then filter while hot to obtain a precipitate. Place the precipitate in deionized water, heat to 80 ° C and stir, then recrystallize at low temperature, and vacuum dry to obtain the product isoindolediacetic acid (BGPD).

[0051] Weigh 2,7-(1,2,4-tetrazolyl)benzophenanthroline tetraketone (4-DTBPT) (0.05mmol 0.02g) in a small beaker, add 4mL N,N'-dimethylformamide (DMF) and sonicate for 5min. Add 2mL of distilled water, weigh isoindolediacetic acid (BGPD) (0.1mmol 0.0332g) in a small beaker containing 4-DTBPT solution, transfer all to an autoclave after dissolution, weigh Co(NO3) 2. 6H2O (0.1mmol, 0.0241g) was placed in an autoclave and reacted at 80°C in an oven for 24h, then cooled to room temperature at a rate of 5°C / h. The autoclave was taken out, and pink strip crystals grew in the solution. The crystals were collected after filtration, and the filtrate was allowed to stand for crystal growth. The yield was 63%. The molecular formula of the crystal is C 52 H 38 CoN 18 O 20 (Co-CP). Infrared spectrum ( Figure 1 ), powder X-ray diffraction spectrum ( Figure 2 ), Coordination environment diagram of Co-CP ( Figure 7) and one-dimensional structure diagram ( Figure 8 ) and 3D stacking plots ( Fig. 9 ) shows that the synthesized product is Co-CP. Figure 3 ) shows the thermal stability of the material; nitrogen adsorption-desorption isotherm and its pore size distribution curve ( Figure 4 ) shows that Co-CP has a certain pore size, which is conducive to the transfer and diffusion of electrolyte ions and improves the electrochemical performance; SEM image ( Figure 5 ) and transmission electron microscopy images ( Figure 6 ) It shows that Co-CP is composed of stacked nano-micron particles. It is used as the active substance of the electrode material, and an electrode sheet is made according to the mass ratio of active substance: acetylene black: binder (PVDF) = 30%: 50%: 20%. The electrode sheet is used as the positive electrode, the lithium sheet is used as the negative electrode, Celgard 2400 is used as the separator, and a 1M mixed solution of ethylene carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC) (volume ratio of 1:1:1) is used as the electrolyte solution. It is assembled into a button cell and its electrochemical performance is examined. The test voltage range is 1.5-4.0V. From Fig.10 From the cyclic voltammogram, we can see that the shapes of the spectra after the second cycle are similar, indicating that the electrode material has good reversibility. Fig.11 The charge-discharge diagram shows that the specific capacity of Co-CP in the first discharge is 247 mAh g -1 . Fig.12 50mAh g -1 The stability diagram of the next cycle is 50 times, and the discharge capacity is still 213mAh g -1 The capacity retention rate is as high as 86.2%, indicating that it has excellent cycle stability. Fig.13 From the AC impedance graph, we can see that the angle of the curve in the low-frequency region is slightly greater than 45°, indicating that the lithium ion migration rate is fast. All these indicate that the material has potential application value as an electrode material for lithium-ion batteries.

[0052] Embodiment 2:

[0053] The preparation method is the same as Example 1, but the ratio of the reactants is changed to 2,7-(1,2,4-tetrazolyl)benzophenanthroline tetraketone (4-DTBPT), isoindolediacetic acid (BGPD) and Co(NO3) 2. The molar ratio of 6H2O was 1:2.2:2.2, and the yield was 64%.

[0054] Embodiment 3:

[0055] The preparation method is the same as Example 1, except that the ratio of distilled water to organic solvent DMF is changed, and the volume ratio of distilled water to organic solvent is 1:2.2, and the yield is 60%.

[0056] Embodiment 4:

[0057] The preparation method is the same as that of Example 1, except that the cobalt salt, 2,7-(1,2,4-tetrazolyl)benzophenanthroline tetraketone (4-DTBPT), isoindolediacetic acid (BGPD) and CoSO 4. The molar ratio of 7H2O was 1:2:2 and the yield was 63%.

[0058] Embodiment 5:

[0059] The preparation method is the same as that of Example 1, except that the cobalt salt, 2,7-(1,2,4-tetrazolyl)benzophenanthroline tetraketone (4-DTBPT), isoindolediacetic acid (BGPD) and CoCl 2. The molar ratio of 6H2O was 1:2:2 and the yield was 65%.

[0060] Embodiment 6:

[0061] The preparation method is the same as Example 1, except that the cobalt salt is changed to a molar ratio of 2,7-(1,2,4-tetrazolyl)benzophenanthroline tetraketone (4-DTBPT), isoindolediacetic acid (BGPD) and (CH3COO)2Co of 1:2:2, and the yield is 61%.

[0062] Embodiment 7:

[0063] The preparation method is the same as Example 1, except that the cobalt salt, 2,7-(1,2,4-tetrazolyl)benzophenanthroline tetraketone (4-DTBPT), isoindolediacetic acid (BGPD) and Co(ClO4) are changed. 2. The molar ratio of 6H2O was 1:2:2, and the yield was 61%.

[0064] Embodiment 8:

[0065] The preparation method was the same as in Example 1, except that the oven cooling rate was changed to 10°C / min, and the yield was 56%.

Claims

1. A one-dimensional cobalt-based coordination polymer material Co-CP, characterized in that: The preparation method comprises the steps of: reacting 2,7-(1,2,4-tetrazolyl)benzophenanthroline tetraketone, isoindolediacetic acid and cobalt salt in N,N'-dimethylformamide and distilled water to generate Co-CP by solvent thermal reaction. The structural formula of isoindolediacetic acid is ; The structural formula of 2,7-(1,2,4-tetrazolyl)benzophenanthroline tetraketone is: 。 2. The method for preparing the one-dimensional cobalt-based coordination polymer material Co-CP according to claim 1, characterized in that: The method comprises the steps of: generating Co-CP by solvent thermal reaction of 2,7-(1,2,4-tetrazolyl)benzophenanthroline tetraketone, isoindolediacetic acid and cobalt salt in N,N'-dimethylformamide and distilled water. The structural formula of isoindolediacetic acid is 。 3. The method for preparing the one-dimensional cobalt-based coordination polymer material Co-CP according to claim 2, characterized in that: The following steps are also included: (1) dissolving 2,7-(1,2,4-tetrazolyl)benzophenanthroline tetraketone in an organic solvent by ultrasonication, adding distilled water and isoindolediacetic acid, and transferring all of the mixture into an autoclave after it is fully dissolved, wherein the molar ratio of 2,7-(1,2,4-tetrazolyl)benzophenanthroline tetraketone to isoindolediacetic acid is 1:2-1:2.2; (2) Add cobalt salt to the autoclave in step (1), heat to react, cool to room temperature after the reaction is completed, and filter to obtain pink strip crystals, which are Co-CP.

4. The method for preparing the one-dimensional cobalt-based coordination polymer material Co-CP according to claim 3, characterized in that: In step (2), the reaction temperature is 80° C. and the reaction time is 24 h; and / or the cooling rate is 5-10° C. / min.

5. The use of the one-dimensional cobalt-based coordination polymer material Co-CP according to claim 1, characterized in that: Used in lithium-ion battery positive electrode materials.

6. A lithium ion battery, characterized in that: The positive electrode component includes the one-dimensional cobalt-based coordination polymer material Co-CP as claimed in claim 1.

Citation Information

Patent Citations

  • Preparation of Coordination Polymer Based on 2, 6-Pyridinedicarboxylic Acid and Its Application in Lithium Ion Battery

    CN109273715A

  • Porous coordination polymer material, and preparation and application thereof

    CN102250129A

  • Polycarbonyl nitrogen heterocyclic organic compound for organic cathode material of lithium battery and preparation method thereof

    CN108711624A